Brand preferences of Perodua cars a case study in Sibu / Saadon Zamhari - Zamhari, Saadon (2006)
A brand is by which a manufacturer uses a name, phrase, design, symbols or combination of these to identify its products and distinguish them from those of competitors. Therefore it is very important for someone to know what a brand is either as a manufacturer, retailers or ourselves as a consumer. For manufacturer or a retailer he needs to know which brand is most preferred by the consumer. For consumers, recognizing a product from its brand allows them to be more efficient shoppers. Consumers can easily recognize and avoid products with which they are dissatisfied, while becoming loyal to other, just by knowing the brand. Generally, the brand often facilitates the consumers in decision-making process. It is the brand of certain products that gave the products the power and value they have in the market place. A powerful brand has high brand equity. Brands have higher brand equity to the extent that they have higher brand loyalty, name awareness, perceived quality, strong brand associations, and other assets such as patents, trademarks and channel relationships.